ON THE “SOLAR SYSTEM SMALL BODIES” ASTROPLATE PROJECT OF THE UKRAINIAN VIRTUAL OBSERVATORY - Shatokhina, S V.; Yizhakevych, O. M.; Protsyuk, Yu. I.; Kazantseva, L. V.; Pakuliak, L. K.; Eglitis, I.; Relke, H.; Yuldoshev, Q. X.; Mullo-Abdolov, A. Sh.; Andruk, V. M. (Одеські астрономічні публікації, 2019)
The UkrVO Joint Digital Archive of astro- plates and the newest digitized data processing services al- lowed us to form a new approach for the creation of catalogs of astrometric and photometric characteristics of the Solar System bodies. Given this, the main goal of this approach was not only to complete the processing with the best possi- ble accuracy of high-quality and unprocessed earlier photo- graphic observations of the Solar System bodies but also to find new original data from these observations. As a result, more than 6,500 new astrometric positions and stellar magnitudes of asteroids, and 3,036 positions of outer planets (Pluto, Uranus, Neptune, Saturn, Jupiter) and their satellites have been determined. Most of the posi- tions obtained from observations of large stellar surveys of the northern sky FON (Kyiv and Kitab parts) and other surveys (MEGA, Equatorial Catalog). The number of new obtained positions of asteroids is comparable to the total number of all positions of aster- oids obtained at the Main Astronomical Observatory of the NAS of Ukraine in 1949-1996. The accuracy of new positions is higher than in traditional determinations from photographic observations, but it cannot be comparable to the accuracy of modern CCD observations. Contrary to traditional classic definitions, digitized im- ages of plates have produced a large number of faint aster- oids down to 17.5 magnitudes, which were discovered in the early 21st century. For some of them, observations are either completely absent or not enough over the certain time interval preceding the moments of their official discoveries. These data can be obtained from photographic observations only. Based on our observations, about 300 such asteroids were found. The collection of missing data on positions over certain time intervals and their analysis can be useful not only for modern ephemeris calculations but also for studying the evolution of asteroid orbits over time. The cooperation between UkrVO and the observatory in Baldone of the University in Latvia, astronomical and astro- physical institutes of Uzbekistan and Tajikistan make it pos- sible to expand this work by involving numerous additional archives of digitized observations and processing services and thus obtaining new original data about the Universe.